Vitamin D status in pregnant women and their newborns in a tertiary care hospital - Kour, Harleen; Gupta, Shashi; Gupta, Swarn K.; Bhagat, Bawa Ram; Singh, Gagan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: In the recent years there has been an increased understanding of the role that vitamin D plays in regulation of cell growth, calcium absorption and immunity and its impact on the developing fetus and maternal health is of significant concern. This study aims at evaluating the Vitamin D status in pregnant women and their newborns. Methods: A cross sectional study was done on 100 pregnant females according to inclusion and exclusion criteria. At the time of delivery, maternal blood was collected, and newborn samples were taken from newborn side of umbilical cord and sent for analysis. Results: The prevalence of Vitamin D deficiency has been found to be 85% of pregnant females and 91% of the newborns. Only 5% of pregnant females and 1% of the newborns showed Vitamin D sufficiency. Maternal and newborn vitamin D levels show a positive correlation. Mean maternal and newborn Vitamin D levels were found to be 16.78±7.04 ng/mL and 11.29±5.75 ng/ml. Conclusions: Vitamin D deficiency is highly prevalent among pregnant women in north India. Low maternal vitamin D levels lead to vitamin D deficiency in the newborns also.